Assessment of Heavy Metal Concentrations in Different Soil Types and Vegetables Grown in Muar, Johor - Rahim, Noorhafizah (2006)
Large areas of land in Muar district, Johor, are especially used for vegetable cultivation. Four major cultivation areas were selected for this study namely, Solok, Pagoh, Sawah Ring and Sengkang which had different types of soils. In these areas, 53 sampling points with a total of 159 soil samples comprising of 66 samples of organic clay and muck (OCM), 42 samples of Holyrood series, 27 samples of Durian series and 24 samples of Jerangau series were collected from the vegetable cultivation areas. The soils were sampled at 0-20 cm, 20-40 cm and 40-60 cm depths. From each of the sampling areas, one sample of vegetable was collected thus, making a total of 53 vegetable samples. Forty-three samples of background topsoils (0-20 cm) from each location that were considered as unaffected or minimally affected by man were sampled.